У.ҲАМДАМ ҲИКОЯЛАРИДА ОЛАМ ВА ОДАМ КОНЦЕПЦИЯСИ - Куронов, С.Д. (SCIENCE and SOCIETY, 2018)
The article deals with the concept of peace and man, reflected in the stories of Ulugbek Hamdam. The author consideris the ideological and artistic essence of the writer’s story in terms of postmodernism. The author’s understanding of the goals and tasks of humanity facing him in the context of globalization is revealed.